2011
DOI: 10.1111/j.1475-6773.2011.01266.x
|View full text |Cite
|
Sign up to set email alerts
|

Population Preferences for Health Care in Liberia: Insights for Rebuilding a Health System

Abstract: OBJECTIVE. To quantify the influence of health system attributes, particularly quality of care, on preferences for health clinics in Liberia, a country with a high burden of disease that is rebuilding its health system after 14 years of civil war. DATA SOURCES/STUDY SETTING. Informed by focus group discussions, a discrete choice experiment (DCE) was designed to assess preferences for structure and process of care at health clinics. The DCE was fielded in rural, northern Liberia as part of a 2008 population-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…Although a growing number of health economists have used RPL models to analyse DCEs in recent years (Hole 2008;Kjaer and Gyrd-Hansen 2008;Negrin et al, 2008;Eberth et al, 2009;Howard and Salkeld 2009;Blaauw et al, 2010;Kimman et al, 2010;Kruk et al, 2010;Scuffham et al, 2010;Sivey et al, 2010;Howard et al, 2011;Kruk et al, 2011;Sweeting et al, 2011;Vujicic et al, 2011;Whitty et al, 2011;Rockers et al, 2012), only a few of these studies have sought to explore respondents' heterogeneity of preferences for DCE attributes. That is, few papers using RPL models have gone beyond the use of random parameters and interacted these random coefficients with socio-demographic characteristics in the model.…”
Section: Introductionmentioning
confidence: 99%
“…Although a growing number of health economists have used RPL models to analyse DCEs in recent years (Hole 2008;Kjaer and Gyrd-Hansen 2008;Negrin et al, 2008;Eberth et al, 2009;Howard and Salkeld 2009;Blaauw et al, 2010;Kimman et al, 2010;Kruk et al, 2010;Scuffham et al, 2010;Sivey et al, 2010;Howard et al, 2011;Kruk et al, 2011;Sweeting et al, 2011;Vujicic et al, 2011;Whitty et al, 2011;Rockers et al, 2012), only a few of these studies have sought to explore respondents' heterogeneity of preferences for DCE attributes. That is, few papers using RPL models have gone beyond the use of random parameters and interacted these random coefficients with socio-demographic characteristics in the model.…”
Section: Introductionmentioning
confidence: 99%
“…[14, 15] These charities, some of which perform cancer surgery, operate under three basic delivery models: short-term surgical trips, self-contained mobile surgical units, and free-standing specialized surgical hospitals. [16] Despite a stated preference by patients in at least some LMICs for government health services,[17] up to 20% of healthcare and 55% of surgery may be provided by the charitable sector. [18–20]…”
Section: Introductionmentioning
confidence: 99%
“…Walters et al found that those with mild or moderate mental distress were more likely to prefer help from informal sources as well as from a general practitioner rather than mental health oriented therapies [27]. Alternatively, in a study of Liberian men and women, Kruk et al found null associations between PTSD and health care preferences [18]. Thus, the association between mental health and value of health care attributes remains unclear.…”
Section: Introductionmentioning
confidence: 99%